The Effect of Activated Carbon From Palm Oil Kernel Shells on Waste Cooking Oil for Soap Production - Yelmiza Yelmiza; Rahma Joni; Muhamad Rokim; Hazra Yuvendius; Elvira Zondra; Arlenny Arlenny (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2026)
This study addresses the existing limitation in integrated waste valorization approaches by combining palm kernel shell–derived activated carbon production, waste cooking oil purification, and solid soap manufacturing within a UMKM-based circular economy model. Unlike previous studies that focus separately on adsorbent synthesis or oil purification, this research evaluates the adsorption performance quantitatively and links it directly to downstream soap quality. Activated carbon was synthesized via controlled pyrolysis (400 °C) followed by KOH activation (800 °C) and characterized using FTIR. The purification process reduced free fatty acid (FFA) content from 2.35 ± 0.02% to 0.43 ± 0.01%, corresponding to an adsorption efficiency of 81.7%. The adsorption capacity was calculated and statistical validation was performed in triplicate experiments. The resulting solid soap exhibited stable pH (8.89 ± 0.05) and satisfactory physical properties. These findings demonstrate the scientific and practical contribution of palm kernel shell activated carbon as a sustainable bioadsorbent supporting circular economy implementation at the UMKM scale.